2019
DOI: 10.1016/j.eclinm.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Pretreatment HIV-1 Drug Resistance in Antiretroviral Therapy-naive Adults in South Africa, 2000–2016: A Pooled Sequence Analysis

Abstract: Background South Africa has the largest public antiretroviral therapy (ART) programme in the world. We assessed temporal trends in pretreatment HIV-1 drug resistance (PDR) in ART-naïve adults from South Africa. Methods We included datasets from studies conducted between 2000 and 2016, with HIV-1 pol sequences from more than ten ART-naïve adults. We analysed sequences for the presence of 101 drug resistance mutations. We pooled sequences by sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 64 publications
6
49
0
Order By: Relevance
“…NAMSAL reported a much lower prevalence of NNRTI resistance (6%) than we did (14%), which is consistent with other data in the region. 41 In NAMSAL, investigators reported no impact of baseline NNRTI resistance on outcomes, although 6/16 failures on EFV had pre-existing NNRTI resistance. In that study, none of the three failures in the DTG arm at 48 weeks had baseline resistance to NNRTIs, the 6% of those that did appeared to suppress during the study.…”
Section: Discussionmentioning
confidence: 99%
“…NAMSAL reported a much lower prevalence of NNRTI resistance (6%) than we did (14%), which is consistent with other data in the region. 41 In NAMSAL, investigators reported no impact of baseline NNRTI resistance on outcomes, although 6/16 failures on EFV had pre-existing NNRTI resistance. In that study, none of the three failures in the DTG arm at 48 weeks had baseline resistance to NNRTIs, the 6% of those that did appeared to suppress during the study.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment drug resistance (PDR) is defined by the WHO as resistance that is detected among people either newly initiating or reinitiating first-line ART [3]. In previous studies, non-nucleoside reverse transcriptase inhibitor (NNRTI) related PDR exceeded 10% in many African settings, supporting the move to include the integrase inhibitor dolutegravir (DTG) in first-line regimens [4,5]. Malawi has set up an effective HIV treatment program.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent use of ART improves immunological response and leads to viral suppression in PLHIV with a subsequent decline in the frequencies of opportunistic infections, including OC [ 29 – 31 ]. The small increase in the prevalence of OC observed between 2012 and 2014 could be due to the increasing number of the “late presenters” [ 32 , 33 ]. That is, patients presenting to care with advanced HIV disease or those already on ART re-presenting to care with advanced HIV disease due to treatment failure [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%